Comparative Study of Two Analytical Methods to the Determination of Boron in Leachate Samples from Sanitary Landfills and Groundwater for Routine Analysis and Feasible On-Site Environmental Monitoring - Rubio-Campos, M (Taylor and Francis Ltd., 2016)
Two analytical methods as inductively coupled plasma optical emission spectrometry (inductively coupled plasma optical emission spectroscopy (ICP-OES)) and azomethine-H UV-Vis-based method were compared statistically, to evaluate their analytical characteristics and applicability to the determination of boron in leachates (complex matrix) from sanitary landfills (SLs) and groundwater (simple matrix) from different sampling points near SLs. Calibration curves and standard addition methods were used for this purpose. Azomethine-H UV-Vis-based procedure has proven better precision and accuracy than ICP-OES. However, statistical analysis (F-test and t-test) does not show significant differences between these two methods, achieving concentration range of up to 10 mg L−1 of the boron in both simple and complex matrices. Due to low cost and gentle-to-operate easy-accessible system, the azomethine-H UV-Vis-based method was therefore proposed (rather than ICP-OES) for routine analysis and for feasible on-site monitoring of boron in SLs, with respect to satisfy Chilean Standard 409 (NCh409) related to drinking water policy. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Landfill; leachate; groundwater; boron; ICP-OES; azomethine-H UV-Vis-based method